(untitled) (Philological Studies, 2019)
The paper deals with a group interjection that is used in the metalinguistic function in Macedonian texts. The research is based on literary texts of the Macedonian language to select interjections and onomatopoeia and to make the Macedonian interjections and onomatopoeia dictionary. We consider the functions of the various subgroups of interjections.